PELATIHAN BAHASA INGGERIS UNTUK KARYAWAN BANK KALSEL - Muhammad Maladi; Soelistijono Boedi; Abdul Kadir; Henny Septiana Amalia; Firdaus, Iqbal; Budi Dermawan (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Ability in using English will have a competitive advantage in building strong business relationships and understanding the needs of international customers. However, many bank employees face challenges in developing their English skills. Some of them may have limited access to adequate learning resources, while others may not have enough spare time to attend formal training. Moreover, some bank employees may feel less confident in using English in real business situations, such as interacting with foreign customers or participating in international meetings.Â  Therefore, through this community service program, we aim to address these obstacles and assist bank employees in developing the English skills necessary for success in an increasingly global banking environment. By providing intensive training, mentoring, and relevant learning resources, we hope to enhance the English competence of bank employees, strengthen their